ChemInform Abstract: Synthesis of New Class of Spirocarbocycle Derivatives by Multicomponent Domino Reaction and Their Evaluation for Antimicrobial, Anticancer Activity and Molecular Docking Studies. Issue 3 (January 2015) - Sudhapriya, N.; Perumal, P. T.; Balachandran, C.; Ignacimuthu, S.; Sangeetha, M.; Doble, Mukesh
Abstract A series of 25 new spirocarbocycles such as (IV), (VI), (VIII) is synthesized including three derivatives (VI) and (VIIId) showing good anticancer activities against A549 cancer cell line.